Creative Intervention for Acrophobia Sufferers through AIVE Concept - Al Hamidy Hazidar; Riza Sulaiman; Shalisah Sharip; Meutia Wardhanie Ganie; Azlin Baharudin; Hamzaini Abdul Hamid; Norshita Mat Nayan (Information, 2021)
This research applies exposure to the visual appearance technology of virtual reality (VR). The motivation for this research is to generate a creative intervention by using regular smartphone devices and implementing them in VR using Google Cardboard as a medium visual display for exposure therapy at high altitudes. The VR application in this research is called acrophobia immersive virtual exposure (AIVE), which utilizes the Unity3D software to develop this treatment therapy application. The utilization of exposure therapy was carried out as a therapeutic medium for acrophobia sufferers. A commissioner was given to measure the usefulness of applications and devices in the VR environment created, and as many as 20 users had tested the VR device. The existing questionnaire was revised to develop a questionnaire for acrophobia sufferers, which was then used as an index measurement in the VR environment. The research is expected to be used to design a simulator and as a therapeutic medium using immersive VR devices in future studies.